On Brokers, Commodification of Information and Liberian Former Combatants. Issue 2 (3rd April 2019) - Käihkö, Ilmari
ABSTRACT: This article investigates research brokers and commodification of information. When combined with inherently asymmetric research relationships and successful gatekeeping, brokers create demand and become indispensable. Potential negative effects of brokerage and commodification of information are discussed through experiences studying former combatants in Liberia. There bargains with brokers who could facilitate access to this hidden population resulted in a vicious circle as brokers confirmed what researchers wanted to hear. The attention to this issue was first brought by subsequent ethnography and participant observation, which also offer the promise of an ethically defensible way of collecting information.